О включениях природных высокотемпературных сплавов со структурами твердофазного распада в коллекторах нефти и газа на больших глубинах - Лукин, А.Е. (Видавничий дім "Академперіодика" НАН України, 2007)
We have discovered the inclusions of natural high-temperature alloys with structures of the type of Widmanstatten figures within deep-lying petroliferous reservoirs.